Pengaruh Penggunaan Pembayaran Digital Dan Digital Marketing Terhadap Keberhasilan Usaha Pada Umkm Pasca Pandemi Covid-19 (Studi Kasus Pada Umkm Konveksi Di Kota Surakarta) - Sidiq, Husaen Bayu; Dewita Puspawati (Fakultas Bisnis, 2025)
Economic growth is a major issue that is a priority for the government to carry out economic development in the future. One form of government foundation in carrying out economic development is to increase entrepreneurship. The Covid-19 pandemic has an impact on changes in various aspects of activities in society, especially in the economic aspect. The impact of digitalization on the micro, small and medium enterprise (MSME) sector, especially on the use of digital payment technology, has begun to develop. The development of digital payments leads to services that can fulfill payment system users. The purpose of this study is to analyze the effect of using digital payments on success and to analyze the effect of using digital marketing on the success of convection MSMEs in Surakarta City after the Covid-19 pandemic. This type of research is quantitative. The population in the study was convection MSMEs in Surakarta City. The sampling technique used Convenience Sampling, namely every MSME that met the criteria and was encountered during data collection. Convenience Sampling is a way of determining the sample by looking for subjects on the basis of things that please or impress the researcher. The analysis technique in this study was assisted using the SPSS 25.0 application. Normality test with Kolmogrov-Smirnov statistical test, Validity Test using Pearson Corelation, reliability test using Croncah Alpha, Multicollinearity Test with VIF and Tolerance values, Heteroscedasticity Test using Spearman rho test. In addition, multiple linear regression analysis to measure the effect of independent variables, and hypothesis testing with the t test and F test to determine the significance of the influence of the independent variable on the dependent variable. The results of this study state that digital payment has no effect on the success of MSME businesses in Surakarta with a sig value. 0.973 and digital marketing has a positive and significant effect on the success of MSME businesses in Surakarta with a sig value. 0,009.